A Prospective Analytical Study of Cervical Cytology in Pregnant Women Attending a Tertiary Hospital (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: cervical cytology; cervical cancer; Papanicolaou smear; cancer screening; epithelial cell abnormality